Descompactando contextos “vazios”: influências das instituições e estratégias não-mercado na relação empresa-sociedade - Sousa, André Luiz Castro de (2020)
Part of the institutionalist theoretical current, when investigating emerging countries, argues in favor of the existence of institutional voids that result from the absence or neglect of institutions at national or local level. These gaps have repercussions in the field of strategy, as they require different organizational responses. This study investigated a local institutional environment in an emerging country, identifying the role of companies in modeling this environment, through two non-market strategies, Corporate Political Activity (CPA) and Corporate Social Responsibility (CSR). In this sense, the objective of the work was to evaluate the influences of the local institutional environment in the definition of non-market strategies and to characterize the role of these strategies in shaping the environment. The empirical research was carried out in the first Industrial District of Fortaleza (IDF), located in the municipality of Maracanaú - CE, where 31 interviews were conducted with business managers, public agents from municipal and state agencies, entities representing the industry and community leaders. Primary data has been supplemented with secondary documents, such as electoral, demographic and historiographic data. The results show that the local institutional environment was shaped under the logic of the emergence of industrialization. The strong role of business-government and interorganizational relations was identified in defining the characteristics of this environment, as well as the recurring dispute of interests between companies and local politicians. The choice to approach three analytical phenomena: territorial ordering, environmental inspection and mutual action plan, was able to validate the manifestations of the mentioned relationships, building analytical alternatives for contexts previously defined as institutionally empty. It was identified that the local institutional environment is conducive to the development of CPA, and its manifestation through electorate building, financial and relational strategies. Regarding CSR, it was found that it is an orientation that is still little present, especially focused on the aspect of philanthropy, to mitigate conflicts and obtain legitimacy. The analyzed non-market strategies suggest the ways in which private actors influence this environment, offering pressure or resistance in the processes of institutional change. The research contributes by showing how companies complement non-market strategies to boost their political capital, conducting the institutional environment according to their expectations, sometimes neglecting the impacts on neighboring communities and the natural environment.